Integrated tourism governance and policy fragmentation in Labuan Bajo: a multi-level governance perspective - Siti Hajar; Heri Wahyudi; Nur Ambia Arma (Otoritas : Jurnal Ilmu Pemerintahan, 2026)
The Labuan Bajo tourism area, designated as a top national super-priority destination, is currently experiencing complex dynamics in tourism development, characterized by accelerated investment, an increase in tourist arrivals, and growing environmental and socio-cultural pressures. This study aims to analyze integrated tourism policy governance practices in Labuan Bajo and to examine structural opportunities and institutional constraints in achieving sustainable and inclusive tourism development. A qualitative case study approach was employed, relying on in-depth interviews, policy document analysis, and field observations. Findings showed that national policy alignment and infrastructure-driven development have enhanced the destination’s competitiveness and global branding. However, governance fragmentation persists due to imbalanced intergovernmental relations, sectoral centric, and weak institutional synchronization. This study identifies three key governance gaps: (1) vertical dissonance between central and local policy implementation, (2) horizontal fragmentation among sectoral agencies, and (3) limited participatory governance, which marginalizes local community involvement. These findings suggest that policy integration remains procedural rather than substantive. This study contributes by proposing an integrated tourism governance model that bridges multi-level governance perspectives and policy integration, emphasizing adaptive and collaborative mechanisms in managing priority destinations.